Design methodology of force feedback laws through helicopter control loop simulation - Prieto-Aguilar, G.; Binet, L.; Rakotomamonju, T. (My University, 2019)
The latest evolution of pilot controllers, referred to as ASSU (Active Side Sticks Units) provides static and dynamic tactile force (or haptic) feedback to the pilot at the grip. Combined with FBW (fly-by-wire), this promising technology has enhanced safety levels compared to the original mechanical linkage systems they have started to replace, while offering vast improved benefits in terms of carefree handling and pilot situational awareness. In the framework of a PhD thesis, the Information Processing and Systems Department (DTIS) of ONERA and SAFRAN Electronics & Defense have started a cooperation to evaluate the interest and the different possibilities offered by the ASSU technology to improve safety and handling qualities of rotary wing aircraft. Up to now, the design and tuning of these functions were essentially performed thanks to numerous simulator sessions or flight tests with pilots. More than just providing a set of values for the required parameters defining the cueing function (hopefully an optimal set of parameters), it is expected that the approach presented here would reduce the number of piloted simulation tests and associated difficulties of the availability of pilots, the significant amount of time and material resources. This paper describes the work done during the first half of the thesis. The main objective of this work is to develop a design methodology based on the simulation of the entire helicopter control loop (also including the pilot in some form) and enabling the definition and parameterization of cueing functions. Moreover, some objective criteria will be defined and used to design the force feedback laws, bringing additional means of evaluation and validation than the classical subjective rating scales.